ode45 Error differential equation system

조회 수: 2(최근 30일)
gorilla3
gorilla3 2017년 10월 13일
댓글: Torsten 2017년 10월 25일
I'm trying to solve a system of differential equations with ode45 but an appears. Could someone help me spot the mistake(s)?
%%Parameters
R_la= 0.4;
R_sa_b= 5.03;
R_sv= 1.32;
R_lv= 0.56;
P_a_b= 100;
P_v= 6;
V_la=1;
V_sa_b= 12;
P_ic= 10;
Ca= 0.205;
k_ven= 0.186;
P_v1= -2.25;
V_vn= 28;
G_q= 3;
tau_q= 20;
Pa_co2_b= 40;
tau_co2= 40;
%%State parameters
F=@(t,V_sa,P1,P2) [ Ca.*(P1-P_ic);
((P_a_b-P1)./(R_la + 0.5 .*R_sa_b) - (P1-P2)./(0.5 .*R_sa_b+R_sv))./Ca;
((P1-P2)./(0.5 .*R_sa +R_sv)-(P2-P_v)./R_lv)./ (1./(k_ven.*(P2-P_ic-P_v1))) ]
[t,V_sa,P1,P2]= ode45(F,[0 10],[0 0 0]);
q= (P1-P2)./0.5 .*R_sa + R_sv ;
F1=@(t,xq,xc) [ (-xq+G_q .*(q-q_b)./q_b)./tau_q ;
(-xc +0.3+3.*tanh(Pa_co2./Pa_co2_b -1.1))./tau_co2 ]
[t,xq,xc]= ode45(F1,[0 10],[0 0 0]);
Error message:
Not enough input arguments.
Error in
CBF_v2>@(t,V_sa,P1,P2)[Ca.*(P1-P_ic);((P_a_b-P1)./(R_la+0.5.*R_sa_b)-(P1-P2)./(0.5.*R_sa_b+R_sv))./Ca;((P1-P2)./(0.5.*R_sa+R_sv)-(P2-P_v)./R_lv)./(1./(k_ven.*(P2-P_ic-P_v1)))]
Error in odearguments (line 87)
f0 = feval(ode,t0,y0,args{:}); % ODE15I sets args{1} to yp0.
Error in ode45 (line 115)
odearguments(FcnHandlesUsed, solver_name, ode, tspan, y0, options, varargin);
Error in CBF_v2 (line 37)
[t,V_sa,P1,P2]= ode45(F,[0 10],[0 0 0]);

채택된 답변

Walter Roberson
Walter Roberson 2017년 10월 13일
Change
F=@(t,V_sa,P1,P2) [ Ca.*(P1-P_ic);
((P_a_b-P1)./(R_la + 0.5 .*R_sa_b) - (P1-P2)./(0.5 .*R_sa_b+R_sv))./Ca;
((P1-P2)./(0.5 .*R_sa +R_sv)-(P2-P_v)./R_lv)./ (1./(k_ven.*(P2-P_ic-P_v1))) ]
[t,V_sa,P1,P2]= ode45(F,[0 10],[0 0 0]);
to
F = @(t, V_saP1P2) [ Ca.*(V_saP1P2(2)-P_ic);
((P_a_b-V_saP1P2(2))./(R_la + 0.5 .*R_sa_b) - (V_saP1P2(2)-V_saP1P2(3))./(0.5 .*R_sa_b+R_sv))./Ca;
((V_saP1P2(2)-V_saP1P2(3))./(0.5 .*R_sa +R_sv)-(V_saP1P2(3)-P_v)./R_lv)./ (1./(k_ven.*(V_saP1P2(3)-P_ic-P_v1))) ];
[t, V_saP1P2] = ode45(F, [0 10], [0 0 0]);
V_sa = V_saP1P2(:,1);
P1 = V_saP1P2(:,2);
P2 = V_saP1P2(:,3);
and similar changes for your F1
  댓글 수: 8
Torsten
Torsten 2017년 10월 25일
Integrating your first equation from t'=0 to t'=t gives
V_sa(t)-V_sa(0)= Ca*(P1(t)-P_ic) - Ca*(P1(0)-P_ic)
This means that V_sa(t) can be expressed by P1(t) as
V_sa(t)=
V_sa(0)+ Ca*(P1(t)-P_ic) - Ca*(P1(0)-P_ic)=
V_sa(0)+Ca*(P1(t)-P1(0))
Consequently, you don't need to include a differential equation for V_sa in your system. The solution can be derived from the solution for P1 by the formula from above.
If you insist on solving a differential equation for V_sa:
d/dt(V_sa) = d/dt(Ca*(P1-P_ic)) = Ca*d/dt(P1)
Now for d/dt(P1), insert the expression from the right-hand side of the differential equation for P1.
Best wishes
Torsten.

댓글을 달려면 로그인하십시오.

추가 답변(0개)

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by